Development of Immunity to Serogroup B Meningococci during Carriage of Neisseria meningitidis in a Cohort of University Students - Jordens, J. Zoe (American Society for Microbiology, 2004)
Understanding the basis of protective immunity is a key requirement for the development of an effective vaccine against infection with Neisseria meningitidis of serogroup B. We have conducted a longitudinal study into the dynamics of meningococcal acquisition and carriage in first-year university students. The detection of carriage of serogroup B meningococci correlated with an increase in detection of serum bactericidal activity (SBA) against both colonizing and heterologous serogroup B strains. Once induced, SBA remained high throughout the study. Although students showed increases in antibodies reactive with capsular polysaccharide and lipopolysaccharide (LPS), these antibody responses were transitory, and their decline was not accompanied by a corresponding decline in SBA. In contrast, there was a significant correlation between the presence of antibodies to the PorA outer membrane protein and SBA against both homologous and heterologous strains. SBA induced by a PorA-negative mutant confirmed the contribution of PorA to heterologous activity. Increases in SBA against a range of serogroup B strains were also observed in students in whom no meningococcal carriage was detected. This heterologous protection could not be associated with the presence of antibodies reacting with capsule, LPS, PorA, PorB, Rmp, Opa, Opc, or pilin, demonstrating that other, as yet unidentified, antigens contribute to the development of immunity to serogroup B meningococci. Identification of such antigens with the ability to induce an effective cross-reactive bactericidal response to a range of strains would be a major step in the production of a universally effective vaccine against infections caused by serogroup B meningococci.